SUSTAINABLE HOSPITALITY MODEL: THE INTEGRATION OF GREEN PRACTICES AND CUSTOMER PERCEIVED VALUE TOWARD GUEST LOYALTY - Ichsan Akmal Mazas akmal; Harbiyah Gani; Aida Fitri (Gabungan Riset Edukasi dan Ekplorasi Teori (GREET), 2026)
The hospitality industry faces increasing pressure to adopt sustainable practices due to growing environmental awareness and shifting consumer preferences. This study aims to develop a Sustainable Hospitality Model by integrating green practices and customer perceived value in enhancing guest loyalty. A quantitative approach was employed using a survey of hotel guests who had stayed at least once within the last year. Data were analyzed using multiple regression to examine both direct and indirect relationships among variables. The findings reveal that green practices have a positive and significant effect on customer perceived value and guest loyalty. Furthermore, customer perceived value mediates the relationship between green practices and guest loyalty. These results confirm that environmentally responsible practices, when integrated with value creation strategies, can strengthen long-term guest loyalty. This study contributes theoretically to the development of sustainable hospitality models and provides practical implications for hotel management in designing customer-oriented sustainability strategies.